2010
DOI: 10.1089/jmf.2009.0203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Frying, Grilling, and Steaming on Amino Acid Composition of Marine Fishes

Abstract: Amino acid and proximate compositions were determined in six raw and cooked marine fish species that are commonly consumed in Turkey. The changes in amino acid and proximate content were found to be significant for all cooking methods in all fish species. Cooking did, in general, significantly increase the contents of essential, semiessential, and other amino acids compared with raw fish species. Grilled Atlantic bonito, anchovy, and bluefish and fried mullet and hake appeared to be more valuable fish dishes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 28 publications
7
53
0
7
Order By: Relevance
“…Oksuz et al (2011), determined the humidity values 79.41% in Upeneus moluccensis and 73.14% in M. surmuletus. Ersoy (2006), found the The moisture values were compared with the previous studies, it was observed that similar results were obtained in some studies (Kalogeropoulos et al 2004;Gumus et al 2009;Oksuz et al 2011), and we found higher values than some studies (Guner et al 1998;Erkan et al 2010b;Polat et al 2009;Tulgar and Berik 2012). We considered that the moisture value differentiations depend on species, season, nutritional regime, size, spawning season, sex, and catching area.…”
Section: Moisturesupporting
confidence: 89%
See 2 more Smart Citations
“…Oksuz et al (2011), determined the humidity values 79.41% in Upeneus moluccensis and 73.14% in M. surmuletus. Ersoy (2006), found the The moisture values were compared with the previous studies, it was observed that similar results were obtained in some studies (Kalogeropoulos et al 2004;Gumus et al 2009;Oksuz et al 2011), and we found higher values than some studies (Guner et al 1998;Erkan et al 2010b;Polat et al 2009;Tulgar and Berik 2012). We considered that the moisture value differentiations depend on species, season, nutritional regime, size, spawning season, sex, and catching area.…”
Section: Moisturesupporting
confidence: 89%
“…In the previous studies, the moisture contents of Mullus barbatus were determined 59.75% by Guner et al (1998), 79.71% by Kalogeropoulos et al (2004), and 79.00% by Gumus et al (2009). Erkan et al (2010b) determined the humidity value 70.25% in Mullus surmuletus. Oksuz et al (2011), determined the humidity values 79.41% in Upeneus moluccensis and 73.14% in M. surmuletus.…”
Section: Moisturementioning
confidence: 99%
See 1 more Smart Citation
“…Erkan et al (2010) observed similar effects of frying on the nutrient content of fish samples. The increase in the fat content was most obvious in the fried fillets, mainly due to the absorption of oil and leaching out of the water during deep-frying (Erkan et al, 2010). According to Saguy & Dana (2003), the cooking oil penetrates into the fillets during frying.…”
Section: Resultsmentioning
confidence: 52%
“…In other studies [Unusan, 2007;Erkan et al, 2010] methionine levels were increased in the fin fishes subjected to conventional and microwave oven-cooked, frying, grilling and steaming processes (achieved at temperatures of 180-190°C). Autoclaving of powdered infant formula at 105°C after being reconstituted in hot water (80°) produced reduced methionine compared to those prepared by conventional methods [Yeung et al, 2006].…”
Section: Non-polar Fatty Acids Concentrationmentioning
confidence: 81%